(untitled) (Global Journal of Management and Business Research, 2016)
In today s competitive global era organizations need to retain efficient and competent employees who perform excellent work in a congenial environment The purpose of the research is to examine the positive and significant impact of continuous learning culture and self efficacy on training effectiveness in the context of insurance sector Three variables were being examined continuous learning culture and self efficacy as an independent variable and training effectiveness as a dependent variable For this purpose data was collected from two hundred employees from various two insurance companies in India especially Delhi through questionnaires Data from target respondents was analyzed in the form of reliability analysis Linear and multiple regression were applied to find the impact of independent variables on dependent variable Findings of the study revealed that continuous learning culture and self efficacy have a positive and significant impact on training effectiveness